How we decide - Lehrer, Jonah (Boston : Mariner Books : Houghton Mifflin Harcourt, 2010)
Offers a fascinating look at the new science of decision-making--and how it can help us make better choices.
Introduction -- The quarterback in the pocket -- The predictions of dopamine -- Fooled by a feeling -- The uses of reason -- Choking on thought -- The moral mind -- The brain is an argument -- The poker hand -- Coda.
Includes bibliographical references (p. [274]-287) and index.
Keywords: Decision making